2010
DOI: 10.1002/jtr.792
|View full text |Cite
|
Sign up to set email alerts
|

‘Gay’ tourists and host community attitudes

Abstract: Despite the growing interest in tourism by gay men, there is little evidence (other than journalistic) of host communities' views towards such tourists. This paper describes a study of such views in a small Mexican beach destination popular with gay tourists. The village is also popular with heterosexual visitors and is known for nude bathing and drug consumption. Interviews were undertaken with a number of residents and revealed disapproval of the gay tourists. This was attributed by residents to overt sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…As a result, unrealistic, generic strategies, competing with a global network of destinations for elusive international travellers (Weaver, 1993, Chapman andSpeake, 2011), are frequently advised. These may additionally fail to take into account local cultural values and expectations, for example, representing a community to outsiders in a way that it finds patronising, (Saarinen, 2006), or targeting visitor groups whose behaviour may be socially disruptive (Hughes et al, 2010). This paper aims to address such gaps in the literature, and investigate domestic tourism in a unique context; that of the small island nation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, unrealistic, generic strategies, competing with a global network of destinations for elusive international travellers (Weaver, 1993, Chapman andSpeake, 2011), are frequently advised. These may additionally fail to take into account local cultural values and expectations, for example, representing a community to outsiders in a way that it finds patronising, (Saarinen, 2006), or targeting visitor groups whose behaviour may be socially disruptive (Hughes et al, 2010). This paper aims to address such gaps in the literature, and investigate domestic tourism in a unique context; that of the small island nation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies tended to focus on specific groups of tourists, such as solo female tourists (Jordan & Aitchison, 2008), gay tourists (Hughes & Carlos, 2010), young backpackers (Maoz, 2006), western tourists (Berno, 1999;Erb, 2000;Evans-Pritchard, 1989;Huang & Lee, 2010) or tourists of a specific nationality (Pizam, 1999;Pizam & Sussmann, 1995;Suntikul et al, 2010;Uriely et al, 2009). Studies like these are helpful, but other samples of tourist types and their origins can be suggested as valuable to build or broaden understanding.…”
Section: Literature Review: Host Gaze Towards Touristsmentioning
confidence: 95%
“…The work of Hughes et al (2010) illustrates that the cultural risks for gay and lesbian tourists may arise not from understandings of sexuality per se, but from notions of the respectful visitor. Hughes et al (2010) in their study of resident attitudes toward men visiting a beach popular with gay men in Mexico found that residents rarely showed strong disapproval or dislike of homosexuality.…”
Section: Riskmentioning
confidence: 99%